Exploring non-alcohol-based disinfectant: virucidal efficacy of arginine and Zinc chloride against feline calicivirus - Kong Li Ying, Marcella; Masirevic, Srdan; Tan, Yong Wah; Marzinek, Jan K.; Fox, Stephen John; Verma, Chandra S.; Bond, Peter J.; Ishida, Yoshiki; Liu, Jiquan; Chua, Chun Song; Chu, Justin Jang Hann (Frontiers in Microbiology, 2025)
IntroductionNorovirus, a leading cause of acute gastroenteritis worldwide, is notably stable in the environment due to its non-enveloped nature. In the absence of effective vaccines or treatments, disinfection remains the primary prevention strategy, highlighting the importance of virucidal efficacy in household care products. Conventional effective disinfectants are predominantly alcohol-based, but alcohol is known to pose health risks, such as skin irritation. This study investigates a non-alcohol-based alternative, specifically a combination of Arginine and Zinc chloride (ZnCl2).MethodsUtilizing MS2 bacteriophage as a surrogate, we identified a robust combination of arginine and ZnCl2 that is effective against Feline Calicivirus (FCV), a mammalian virus surrogate model for Norovirus.ResultsOur results determined a 5 min contact time at pH 11 as optimal, achieving significant virucidal activity against FCV without pH-induced reversibility. Dynamic Light Scattering (DLS) and transmission electron microscopy (TEM) analyses suggested that the mechanism of action for the Arg-Zn2+-Arg complex does not involve capsid disruption. Further insights from molecular modeling studies revealed that the complex potentially inhibits FCV by occupying a key capsid binding pocket essential for Junctional Adhesion Molecule (JAM) receptor engagement, thereby preventing viral entry.ConclusionThese findings allow us to propose a novel and non-alcohol-based virucidal approach against viruses from the Caliciviridae family, highlighting the potential of Arg-Zn2+-Arg complexes in public health protection.